Overview on the performance of Brazilian broilers (1990 to 2009) - Patricio, IS; Mendes, Ariel Antonio [UNESP]; Ramos, Alcides de Amorim [UNESP]; Pereira, Danilo Florentino [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2012)
This article describes the genetic evolution of commercial broilers between 1990 and 2009, considering live performance, in particular, in terms of weight gain and feed conversion ratio. In order to determine if the assumption that the relationship between body weight gain and feed conversion ratio is increasing and positive, information on all broiler strains reared in Brazil were collected from several companies present in five Brazilian regions. This survey aimed at evaluating broiler live performance as a function of genetic improvement with time. Broiler performance improved, as shown by the statistical differences obtained for the following parameters: livability, live weight, daily weight gain, feed conversion ratio, and production efficiency index between 1990 and 2009. However, live weight gain and feed conversion ratio are emphasized due to the significant differences found along the studied period.
Keywords: Poultry production; production efficiency; genetics; livability